2011
DOI: 10.1161/atvbaha.110.213934
|View full text |Cite
|
Sign up to set email alerts
|

Flavopiridol Protects Against Inflammation by Attenuating Leukocyte-Endothelial Interaction via Inhibition of Cyclin-Dependent Kinase 9

Abstract: Objective-The cyclin-dependent kinase (CDK) inhibitor flavopiridol is currently being tested in clinical trials as anticancer drug. Beyond its cell death-inducing action, we hypothesized that flavopiridol affects inflammatory processes. Therefore, we elucidated the action of flavopiridol on leukocyte-endothelial cell interaction and endothelial activation in vivo and in vitro and studied the underlying molecular mechanisms. Methods and Results-Flavopiridol suppressed concanavalin A-induced hepatitis and neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 26 publications
6
63
0
Order By: Relevance
“…We previously provided evidence that CDK9 is important for the activation of a subset of rapidly inducible NF-B-dependent cytokine genes (69). This work was extended in studies examining the effect of blocking CDK9 activity and found decreased ICAM-1 expression in human endothelial cells and reduced leukocyte recruitment (72). Our present study further demonstrates that CDK9-initiated transcription elongation also plays a major role in the IRF3-induced ISG response.…”
Section: Discussionsupporting
confidence: 74%
“…We previously provided evidence that CDK9 is important for the activation of a subset of rapidly inducible NF-B-dependent cytokine genes (69). This work was extended in studies examining the effect of blocking CDK9 activity and found decreased ICAM-1 expression in human endothelial cells and reduced leukocyte recruitment (72). Our present study further demonstrates that CDK9-initiated transcription elongation also plays a major role in the IRF3-induced ISG response.…”
Section: Discussionsupporting
confidence: 74%
“…An increasing number of agents have been identified to interfere with the pathogenicity of atherosclerosis by targeting CDKS. Of these, CDK9 has been shown to exhibit marked characteristics in controlling inflammation (12). In a previous study (unpublished data), results of the 2-D proteomics analysis revealed that CDK9 was highly expressed in the serum of patients with atherosclerosis.…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, it effectively limited murine hepatitis induced by concanavalin A (ConA), which triggers a strong and rapid leukocyte-dependent inflammatory liver injury (38). Roscovitine protected against acute graft-versus-host disease by blocking the clonal expansion of T cells (12) and against glomerulonephritis by inhibiting the proliferative response of T and B cells (39). Thus, the anti-inflammatory effect of CDKs inhibitors has been ascribed to its inhibition of the proliferation and induction of cell death in immune cells and.…”
Section: Cdk9 With T Cells and Monocytesmentioning
confidence: 99%
See 2 more Smart Citations